Procesos administrativos y su incidencia en las estrategias comerciales de la empresa publivision de la ciudad de Babahoyo - Tomalá Coloma, Tomalá Coloma (2014)
The present thesis proposes a "Administrative Processes and its incidences in the commercial strategies of the company Publivisión of the city of Babahoyo, how the types of activities of advertising services are in growth and new competitors are born in different lines of publicity. The lack of Organization has taken the administrator of the company Publivisión to make random decisions regarding the turn of the business, decisions that have been made without a planning based on hunches and instinct but not having the security that it will work neither marketing knowledge...